Limitations of the use of concrete bulk resistivity as an indicator for the rate of chloride‐induced macro‐cell corrosion. (16th February 2017) - Hornbostel, Karla; Elsener, Bernhard; Angst, Ueli M.; Larsen, Claus K.; Geiker, Mette R.
Abstract : An experimental setup was designed to study the impact of concrete bulk resistivity on the rate of chloride‐induced reinforcement corrosion. Small pieces of mild steel were used to simulate pits (anodes) that form when chlorides come into contact with the reinforcement. The galvanic current was measured between the simulated anodes and a large cathode network. Comparisons were made between the corrosion rates calculated from the galvanic currents and the bulk resistivity. The bulk resistivity was varied using two mortar mixes (made of plain Portland cement and a Portland cement—fly ash blend), which were exposed in different temperature and moisture conditions. Despite a high scatter in the results, it was clear that the relationship between bulk resistivity and corrosion rate depended on the mortars tested. The findings presented in this article and the accompanying work strongly indicate that bulk resistivity alone does not provide sufficient information for assessment of the corrosion rate for chloride‐induced macro‐cell corrosion.